0215 Impact of sleep inertia on visual search performance during combined sleep restriction and circadian misalignment. (25th May 2022) - Adkins, Matthew; Schreiber, Austin; Sprecher, Kate; Burke, Tina; Ritchie, Hannah; Wright, Kenneth
Abstract: Introduction: Circadian phase and homeostatic sleep drive affect selective visual attention during sleep inertia (SI), a period of cognitive performance decrement upon awakening that dissipates with time. This study examined the combined effects of circadian misalignment and sleep restriction on visual search performance during SI. Methods: Twenty adults (mean±standard deviation [SD] age 25.7±4.2 years; 12M, 8F) completed a 39-day protocol. Prior to a 4-day in-laboratory visit, participants maintained habitual 8h sleep schedules for 2 weeks at home. In-laboratory sleep opportunities (1 per day) were timed to induce varying levels of both circadian misalignment and sleep restriction: 8h on night 1, 3h on night 2, and 3h on mornings 3 and 4. After 3 days of recovery sleep at home (unscheduled), participants repeated the entire protocol. SI was assessed with the Serial Visual Search Task, a measure of selective visual attention, ~ 1, 16, and 31 min after electroencephalogram (EEG) verified awakening following each 3h sleep opportunity. The task required participants to determine whether a target was present or absent among nontarget distractors. Outcomes included median reaction times (RT) and number of missed targets. Sleep opportunities with ≥4.5 min of EEG-verified wakefulness in the 30 min prior to scheduled awakening were excluded from analysis. Data were analyzed with mixed-model ANOVA. Results: Mean±SD average amount of wakefulness in the 30 min and 10 min prior to SI testing was 1.2±0.11 and 0.43±0.06 minutes, respectively. Following all sleep opportunities, median RT for overall correct responses and for correct response to target absent trials improved with time since awakening (all p<0.05). In contrast, median RT for correct responses to target present trials improved and number of missed targets worsened with time since awakening following the morning 3 sleep opportunity only (all p<0.05). Conclusion: Reaction speed was impaired during SI regardless of circadian timing or level of homeostatic sleep drive, whereas missing targets appears to be dependent upon circadian phase and the level of homeostatic sleep debt. These findings have important implications for military and first responders. Support (If Any): Office of Naval Research MURI N00014-15-1-2809; NIH TR001082; Undergraduate Research Opportunities Grant, University of Colorado Boulder.